Echocardiographic Diagnostics of Myocardial Infarction in Newborns - G. V. Revunenkov; K. A. Valyalov (Union of pediatricians of Russia, 2015)
Early and correct diagnostics of myocardial infarction in newborns is impossible without modern instrumental methods, among which echocardiography is the leading one. Hypokinesia, akinesia or dyskinesia of local segments of the heart ventricular wall is determined with echocardiography. We examined a 3-days-old baby with circulatory failure requiring cardiotonic support. On auscultation there was a heart murmur. It was an intracardiac conduction disoder and infarction-like changes on ECG, however, a convincing evidence to interpret the patient's condition as myocardial infarction has not been received. Therefore, it was decided to conduct echocardiography. According to the results of echocardiography the presence of hyperechogenic diskinetic locus in the apical segment of the right ventricle (post-infarction scar), a local pericardial effusion in the same projection, hyperechogenic movable mass (thrombus) in the apical segment of the right ventricle were determined that together with the results of the ECG allowed us to set diagnosis myocardial infarction. Transthoracic echocardiography is one of highly informative methods; the data obtained allowed to correctly interpret the clinical picture of heart failure and to reveal the cause of the patien'st dependance on cardiotonic support.